Tractors at work - Peppas, Lynn. (St. Catharines, Ont. ; New York : Crabtree Pub. Co., 2011)
Tractors at Work uses detailed photographs and decodable text to introduce readers to different tractor models and the kinds of work different tractors can do.
Hard-working tractors -- Tractor power -- Slow and steady -- Hitchin' a ride -- Front-end jobs -- Big wheels -- Making tracks -- CUT-out for smaller jobs -- Utility farm tractors -- Monster tractors -- Backhoe -- Bulldozer -- Pushback tractors -- Tractor pulls.
Includes index.
Includes index.
Keywords: Tractors -- Juvenile literature; Tractors